PELATIHAN JARINGAN KOMPUTER DENGAN MENGGUNAKAN MIKROTIK PADA SMKN 1 PRINGGASELA - Muhammad Khulaimi; Muhamad Masjun Efendi; Muladi, Agum; Mujahadah, Nur (LPP ARROSYIDIN, 2024)
Network installation is an important insight for everyone in the digital age, especially for those who study computer networks academically. In reality, knowledge and application related to network installation are still often overlooked in daily internet practices. Insights on network security are important for vocational school students to learn in order to build a more comprehensive thinking paradigm, that building a network is not only about building connections between devices, but also ensuring that every information and privacy can be well maintained. At SMKN 1 Priggasela there is a Computer Network Department, but there is no special material that teaches about network installation in accordance with current industrial needs.